2020
DOI: 10.1590/1984-0462/2020/38/2018332
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors With the Isolated and Simultaneous Presence of Overweight and Abdominal Obesity in Adolescents

Abstract: Objective: To analyze the sociodemographic and lifestyle factors associated with excessive weight (EW), abdominal obesity (AO) and the simultaneous presence of EW and AO in adolescents from Southern Brazil. Methods: Cross-sectional study with 583 adolescents (11 to 17 years old) of Criciúma, Santa Catarina, Brazil. EW was assessed by body mass index (BMI) and AO by waist circumference (WC). The independent variables analyzed were gender, age, maternal schooling, balanced diet, physical activity, cigarette u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
3
0
6
Order By: Relevance
“…Internet addicted adolescents had also elevated risk of obesity in one study [19]. However, several other studies reported no signi cant association between obesity and screen time was observed [22,27,47]. The possible strong reason for this inconsistency, is the type of screen (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Internet addicted adolescents had also elevated risk of obesity in one study [19]. However, several other studies reported no signi cant association between obesity and screen time was observed [22,27,47]. The possible strong reason for this inconsistency, is the type of screen (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Or, in some of the studies, only watching television or playing video games of more than three hours per day increased obesity risk among adolescents [24][25][26]. More surprisingly, a non-signi cant reduced risk of excess weight by increased screen time of more than 4 hours/day was observed in De-Lima et al study [27] (0.87 CI = 0.59-1.30). According to the review of literature, a great between-study heterogeneity was observed in studies that evaluated the association between screen time and obesity among adolescents.…”
mentioning
confidence: 97%
“…Among the biological determinants, that adolescents of a younger age group were more likely to be excessive weight, corroborating with a previous study. 22 It is possible that in this group older adolescents are more concerned with weight and body shape, leading them to perform restrictive behaviors (restrictive diets and fasting) and this may have protected them from being overweight. Because the cult of female thinness is widespread in the media, concerns about body weight are more frequent among women and this may have been the reason why the prevalence of overweight was lower in females when compared to males in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo o Instituto Brasileiro de Geografia e Estatística o percentual de adultos com sobrepeso e obesidade foi de 14,8%, e entre os adolescentes foi de 21,5% de sobrepeso e 4,9% de obesidade. Em pesquisa realizada entre os anos de 2013 a 2014 com adolescentes de 12 a 17 anos constatou-se que 17,1% tinham sobrepeso e 8,4% eram obesos (DE LIMA et al, 2020).…”
Section: Introductionunclassified